Histopathological biomarking changes in the internal organs of Tilapia (Oreochromis niloticus) and catfish (Clarias gariepinus) exposed to heavy metals contamination from Dandaru pond, Ibadan, Nigeria - Oluseye Oladapo Abiona; Adebanjo Jacob Anifowose; Shola Hezekiah Awojide; Oluwaseun Cecilia Adebisi; Babatunde Taiwo Adesina; Mabel Omowumi Ipinmoroti (Journal of Taibah University for Science, 2019)
The study assessed histopathological alterations in the organs of Oreochromis niloticus (Nile tilapia) and Clarias gariepinus (Catfish) harvested from Dandaru Pond, Ibadan, Nigeria. The histopathological effects were evaluated through biomarkings and heavy metals measurements of the fish organs and tissue. Results showed the kidney with sign of coagulated necrosis of the renal tubules. In the liver, there were hepatocytes which appeared foamy and contained large-sized vacuoles. The gills appeared with some congestion in their capillaries in addition to numerous bluish staining walled-off structures. There was severe thinning of the myocardial fibres in the fish heart. The chambers were moderately congested. The fish organs contained 0.06–0.90 µg/g lead. The Pb concentrations and those of manganese and iron exceeded the WHO permissible limit in fish. It is conclusive that the bioaccumulated heavy metals in the tissue and fish organs consequently impaired their histopathological condition, and thus affect fish health status.